The contents of visual experience - Siegel, Susanna (New York ; Oxford : Oxford University Press, 2011)
What do we see? We are visually conscious of colors and shapes but are we also visually conscious of complex properties such as being John Malkovich? In this book, Susanna Siegel develops a framework for understanding the contents of visual experience and argues that these contents involve all sorts of complex properties.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Vision; Experience; Philosophy of mind